2007
DOI: 10.1038/sj.cgt.7701057
|View full text |Cite
|
Sign up to set email alerts
|

Proof concept for clinical justification of network mapping for personalized cancer therapeutics

Abstract: To identify signature targets associated with patient-specific cancer lesions based on tumor versus normal tissue differential protein and mRNA coexpression patterns for the purpose of synthesizing cancer-specific customized RNA interference knockdown therapeutics. Analysis of biopsied tissue involved two-dimensional difference in-gel electrophoresis (2D-DIGE) analysis coupled with MALDI-TOF/TOF mass spectrometry for proteomic assessment. Standard microarray techniques were utilized for mRNA analysis. Priority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…116 However, highly connected targets do allow for 'attack vulnerability.' In other words, the disordered circuitry characteristic of malignancy results in a change, such that the otherwise robust oncogenic process can become, almost paradoxically, more highly dependent on a specific rewired pathway ('pathway addiction').…”
Section: Theoretical and Practical Considerations Of Mirna-based Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…116 However, highly connected targets do allow for 'attack vulnerability.' In other words, the disordered circuitry characteristic of malignancy results in a change, such that the otherwise robust oncogenic process can become, almost paradoxically, more highly dependent on a specific rewired pathway ('pathway addiction').…”
Section: Theoretical and Practical Considerations Of Mirna-based Cancmentioning
confidence: 99%
“…In other words, the disordered circuitry characteristic of malignancy results in a change, such that the otherwise robust oncogenic process can become, almost paradoxically, more highly dependent on a specific rewired pathway ('pathway addiction'). 116 This thesis forms the theoretic basis of attempting to correct the tumor phenotype through the targeting of the dominant, offending oncogenic pathway.…”
Section: Theoretical and Practical Considerations Of Mirna-based Cancmentioning
confidence: 99%
“…Based on differential proteogenomic signaling assessments of patients from our program [13,14], as well as published literature by others, there is a sound rationale for the therapeutic targeting of STMN1 in cancer patients [15]. Stathmin is highly expressed in a variety of human malignancies [16,17] and has been shown to be upregulated in multiple cancers.…”
Section: Relevance Of Stmn1 To Cancermentioning
confidence: 99%
“…The bifunctional construct bi-sh-STMN1 is directed against Stathmin1 (STMN1), a gene target candidate that is overexpressed in human cancer lines and was shown by us to be differentially overexpressed in cancer patients, based on mRNA and protein couplet signals in tumor/ normal tissue specimen analysis. 13 STMN1 is critically involved in mitotic spindle formation. 14,15 Previously, studies have shown that STMN1 knockdown by conventional siRNA resulted in G 2 /M cell cycle arrest, inhibition of clonogenicity and markedly increased apoptosis.…”
Section: Introductionmentioning
confidence: 99%